Security and skills: the two key issues in health worker migration. - Bidwell, P; Laxmikanth, P; Blacklock, C; Hayward, G; Willcox, M; Peersman, W; Moosa, S; Mant, D (2014)
BACKGROUND: Migration of health workers from Africa continues to undermine the universal provision of quality health care. South Africa is an epicentre for migration--it exports more health workers to high-income countries than any other African country and imports health workers from its lower-income neighbours to fill the gap. Although an inter-governmental agreement in 2003 reduced the very high numbers migrating from South Africa to the United Kingdom, migration continues to other high-income English-speaking countries and few workers seem to return although the financial incentive to work abroad has lessened. A deeper understanding of reasons for migration from South Africa and post-migration experiences is therefore needed to underpin policy which is developed in order to improve retention within source countries and encourage return. METHODS: Semi-structured interviews were conducted with 16 South African doctors and nurses who had migrated to the United Kingdom. Interviews explored factors influencing the decision to migrate and post-migration experiences. RESULTS: Salary, career progression, and poor working conditions were not major push factors for migration. Many health workers reported that they had previously overcome these issues within the South African healthcare system by migrating to the private sector. Overwhelmingly, the major push factors were insecurity, high levels of crime, and racial tension. Although the wish to work and train in what was perceived to be a first-class care system was a pull factor to migrate to the United Kingdom, many were disappointed by the experience. Instead of obtaining new skills, many (particularly nurses) felt they had become 'de-skilled'. Many also felt that working conditions and opportunities for them in the UK National Health Service (NHS) compared unfavourably with the private sector in South Africa. CONCLUSIONS: Migration from South Africa seems unlikely to diminish until the major concerns over security, crime, and racial tensions are resolved. However, good working conditions in the private sector in South Africa provide an occupational incentive to return if security did improve. Potential migrants should be made more aware of the risks of losing skills while working abroad that might prejudice return. In addition, re-skilling initiatives should be encouraged.